PENTINGNYA PENCATATAN BISNIS DAN LAPORAN KEUANGAN UNTUK PENINGKATAN DAYA SAING PRODUK BERBASIS PELATIHAN DAN PENDAMPINGAN PADA USAHA BATIK SEKAR ARUM DESA BULULAWANG, KECAMATAN BULULAWANG KABUPATEN MALANG - Ita Rifiani Permatasari (Publisher UPT P2M Politeknik Negeri Malang, 2017)
The purpose of this activity is to provide guidance and counseling about the importance of business recording, determining the cost of production, determining of the selling price and financial statements for improving product competitiveness in Sekar Arum Batik. Sekar Arum Batik Business, located at RT 25, RW 3 Bululawang Village, Bululawang Sub-district, Malang Regency, is one of the small household group, assisted by Posdaya Polinema, with 30 housewife employees. There are some obstacles in the implementation of this training activities, such as training materials that are new to them, changing the habits of those who never recorded every transaction because they only rely on their memory. The supporting factor is the participants are aware of the benefits of an adequate record in business transactions, not only necessary for internal purposes, but also external purposes, such as lender banks, investment partners, suppliers offering credit and tax officers.